2022
DOI: 10.51414/sei2022.010
|View full text |Cite
|
Sign up to set email alerts
|

Charting a youth vision for a just and sustainable future

Abstract: This report is a companion to the independent scientific report Stockholm+50: Unlocking a Better Future (SEI & CEEW, 2022) prepared ahead of the UN international meeting ‘Stockholm+50: a healthy planet for the prosperity of all – our responsibility, our opportunity’. The report is meant to capture the perspectives of youth, authored by a group of early-career researchers at Stockholm Environment Institute (SEI) and the Council on Energy, Environment and Water (CEEW).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Let us bear in mind the difficult truth that ‘a child born in 2020 will experience on average twice as many wildfires, 2.6 times as many drought events, 2.8 times as many river floods and 6.8 times more heatwaves across their lifetime, compared to a person born in 1960’ (Aggarwal et al . 2022, 60). The ethical ACD curriculum must move with the times and must include consideration of the environment and climate emergency.…”
Section: Environmentally Responsible Acd Education For Allmentioning
confidence: 99%
See 2 more Smart Citations
“…Let us bear in mind the difficult truth that ‘a child born in 2020 will experience on average twice as many wildfires, 2.6 times as many drought events, 2.8 times as many river floods and 6.8 times more heatwaves across their lifetime, compared to a person born in 1960’ (Aggarwal et al . 2022, 60). The ethical ACD curriculum must move with the times and must include consideration of the environment and climate emergency.…”
Section: Environmentally Responsible Acd Education For Allmentioning
confidence: 99%
“…Importantly, it has been found that a lack of environmental and climate literacy among young people is often due to ‘an absence of support by community and government, lack of adequate funding and time for field visits, disinterest among students, lack of teacher training, limited access to quality content, and rigid classroom training systems resistant to curriculum revision’ (Anderson & Jacobson 2018, as cited in Aggarwal et al . 2022, 51). The problem of lack of teacher training would be partly addressed via my recommendation for continuing professional development for ACD teachers, which addresses the environment and climate emergency.…”
Section: Greening the Nsead Manifestomentioning
confidence: 99%
See 1 more Smart Citation